Does the imbalance in the apolipoprotein E isoforms underlie the pathophysiological process of sporadic Alzheimer's disease?. Issue 1 (28th July 2022) - Lozupone, Madia; Imbimbo, Bruno Pietro; Balducci, Claudia; Lo Vecchio, Filomena; Bisceglia, Paola; Latino, Raffaela Rita; Leone, Maurizio; Dibello, Vittorio; Solfrizzi, Vincenzo; Greco, Antonio; Daniele, Antonio; Watling, Mark; et al.
Abstract: Human apolipoprotein E (apoE) is a 299‐amino acid secreted glycoprotein binding cholesterol and phospholipids, and with three common isoforms ( APOE ε2, APOE ε3, and APOE ε4). The exact mechanism by which APOE gene variants increase/decrease Alzheimer's disease (AD) risk is not fully understood, but APOE isoforms differently affect brain homeostasis and neuroinflammation, blood–brain barrier (BBB) permeability, glial function, synaptogenesis, oral/gut microbiota, neural networks, amyloid beta (Aβ) deposition, and tau‐mediated neurodegeneration. In this perspective, we propose a comprehensive interpretation of APOE ‐mediated effects within AD pathophysiology, describing some specific cellular, biochemical, and epigenetic mechanisms and updating the different APOE ‐targeting approaches being developed as potential AD therapies. Intracisternal adeno‐associated viral‐mediated delivery of APOE ε2 is being tested in AD APOE ε4/ε4 carriers, while APOE mimetics are being used in subjects with perioperative neurocognitive disorders. Other approaches including APOE ε4 antisense oligonucleotides, anti‐ APOE ε4 monoclonal antibodies, APOE ε4 structure correctors, and APOE –Aβ interaction inhibitors produced positive results in transgenic AD mouse models.